Anti-inflammatory potential of lemongrass leaves in wound healing - Hasibuan, Patimah Fitriansyari; Tambunan, Andika Zayani; Mutia, Maya Sari (Jurnal Prima Medika Sains, 2023)
The inflammatory stage is a normal phase of wound healing; however, inflammation can become chronic and lasts for months or years. This is a post-test with control group design study, divided with 20 male white rats into 4 groups: control group (K), treatment group 1 (P1), treatment group 2 (P2), and treatment group 3 (P3). Lemongrass leaf extract gel, simplicia leaves, stems, and roots of citronella were extracted by maceration using a 1:5 ratio of simplicia to solvent. Gel was applied twice a day (morning and evening) to each group, adhering the formulation. Macroscopic observations were made to assess the wound condition and incision length. The length of the incision wound was measured using a ruler every two days for a span of fourteen days. As the sample size was less than 50, a normality test was performed using the Shapiro-Wilk test, followed by a One-way ANOVA and a Post Hoc test. The study found that wound healing was slowest in the control group but faster in the groups treated with 10% and 15% lemongrass leaf extract. Secondary metabolites at a concentration of 15% had a positive impact on wound healing, whereas at lower concentrations, they only inhibited microorganisms, making them less effective for wound healing.